Pemberdayaan Keluarga dan Masyarakat Melalui Pelatihan Komunikasi Dalam Keluarga yang Mengedepankan Kepentingan Anak - Rahayu, Ety (UI Scholars Hub, 2012)
To be able to realize child welfare, the family, society and the government should pay attention to the rights and needs of children. To ensure the psychological dan social development, children need love, understanding, recreational atmosphere, creative stimulation, self-actualization, and intellectual development. Therefore they require early socialization and basic education, the teaching of social responsibility, social roles and basic skills in order to become useful citizens. Children from poor families are often raised with parenting less conducive to their growth and development. One of the efforts undertaken is through communication training for mothers from poor families. Through this training the parents are expected to create an atmosphere conducive to the development of children.